2021
DOI: 10.1093/ecco-jcc/jjab165
|View full text |Cite
|
Sign up to set email alerts
|

Use of Faecal Transplantation with a Novel Diet for Mild to Moderate Active Ulcerative Colitis: The CRAFT UC Randomised Controlled Trial

Abstract: Background We evaluated whether integration of novel diets for donors and patients in addition to fecal transplantation (FT) could increase FT remission rate in refractory ulcerative colitis (UC). Methods This was a blinded randomized controlled trial in adults with active UC, defined by a simple clinical colitis activity index (SCCAI) of ≥5 and ≤ 11 and endoscopic Mayo score 2-3, refractory to medication. Group 1 received fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
53
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 30 publications
4
53
1
Order By: Relevance
“…FMT was safe and no serious adverse events were reported. The minor adverse events were similar to that reported by other RCTs 13 30–33…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…FMT was safe and no serious adverse events were reported. The minor adverse events were similar to that reported by other RCTs 13 30–33…”
Section: Discussionsupporting
confidence: 88%
“…There are certain other novel findings. The study design was different from previous RCTs, as the comparator arm here was optimisation of medical therapy, rather than a true placebo, while, except for one, previous RCTs have either included placebo or autologous FMT as a comparator arm 13 30–34. This accounted for relatively higher clinical/endoscopic remission and response rates in the comparator arm compared with previous RCTs (which reported positive results with FMT).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another weakness of the study is that we did not perform colonoscopy in order to evaluate mucosal healing. However, recently, we have published a randomized controlled trial in adult patients with active refractory UC, showing that the UCED alone appeared to achieve mucosal healing versus single-donor fecal transplantation with or without diet, as mucosal healing (Mayo 0) was achieved only in the group that received the UCED (3/15, 20%) vs. 0/36 of the patients who received fecal transplantation (p = 0.022) [51]. However, we emphasize that, without a placebo group, caution needs to be taken in interpreting our results, as some of the response could be mediated by placebo effects.…”
Section: Discussionmentioning
confidence: 99%
“…UCED was designed to alter dietary components that may adversely affect goblet cells, mucus permeability, and microbiome composition, which were previously linked to UC. The research team also reported in another study that UCED alone appeared to achieve higher clinical remission and mucosal healing than FMT with or without diet [ 34 ], and a randomized controlled trial is currently investigated. The diet intervention was not included in our study; however, the participants were required to take less saturated fat and food additives during the 8 weeks of follow-up.…”
Section: Discussionmentioning
confidence: 99%